Real-world safety of HPV vaccines over 18 y: A comprehensive analysis of U.S. VAERS reports - Yonglong Su; Yirong Huang; Jinbao Wei; Xinjin Wang; Yanyan Zhou; Xiaohong Wu; Honghong Fu (Human Vaccines & Immunotherapeutics, 2025)
Human papillomavirus (HPV) vaccination is central to preventing cervical and other HPV-associated cancers. Although clinical trials have established favorable safety profiles, long-term, brand-specific real-world data remain limited. We evaluated adverse events (AEs) reported to the U.S. Vaccine Adverse Event Reporting System (VAERS) for Cervarix® (bivalent), Gardasil® (quadrivalent), and Gardasil-9® (9-valent) between January 2006 and December 2024. Domestic VAERS reports listing ≥1 HPV vaccine were extracted, deduplicated, and classified by brand. Disproportionality analyses were performed using reporting odds ratios (RORs) and 95% confidence intervals (CIs), adjusting for multiplicity with a 5% Benjamini – Hochberg false discovery rate (FDR). Time-to-onset was assessed with Kaplan–Meier analysis. This analysis of 76,575 HPV vaccine adverse event reports shows improving safety profiles across vaccine generations. Serious adverse events decreased significantly from Cervarix® (33.4%) to Gardasil® (16.2%) to Gardasil-9® (7.8%). The most common signals were presyncope for Cervarix® (ROR 11.5) and administration errors for Gardasil® and Gardasil-9®, including inappropriate scheduling (ROR 19.5) and incorrect storage (ROR 12.1). Most adverse events (82.9%) occurred within 7 d post-vaccination, with 62.5% occurring on the same day. Gardasil-9® exhibited the narrowest IQR for time to onset (0–1 d), compared to other HPV vaccines. HPV vaccines demonstrate a consistent, favorable safety profile in U.S. real-world practice. Most reported AEs were acute vasovagal reactions, and strongest signals reflected preventable errors. Strengthening provider education in cold-chain management and schedule adherence may further enhance vaccine safety. Continued active surveillance is recommended.